The Effect of Blended Learning On Physics Learning Outcomes of Students in SMA N 1 Sewon Class XI Rotation Dynamics - Widyasari, Rohmah Riya; Purwanto, Joko (Proceeding International Conference on Science and Engineering, 2020)
This study aims to determine the effect of blended learning on students' physics learning outcomes on rotational dynamics material. This research is a Quasi Experiment with Group Design Pretest-Posttest Control. The research variables include the independent variables in the form of blended learning and the dependent variable in the form of learning outcomes. The population in this study were all grade XI students of SMA N 1 Sewon in the 2019/2020 school year. Sampling was done using the Simple Random Sampling technique, selected class XII IPA 5 as an experimental class and class XII IPA 6 as a control class. Data collection techniques with the form of tests with the test instruments used are written tests in the form of multiple-choice questions. Data analysis techniques used are nonparametric statistics, Normalized-Gain, and effect size. The results showed that blended learning did not affect students' learning outcomes in rotational dynamics material. Treatment is said to be influential if there is a difference in the increase in student physics learning outcomes between the experimental class and the control class as indicated by the rejection of H0 in testing the hypothesis using the U-test. Based on the U-test analysis of the posttest data of the experimental class and the control class the significance value obtained is 0.074, which means it is greater than the significance level so that the given H0 is received or there is no influence from blended learning treatment. The average N-gain of the experimental class was 0.38 and the control class was 0.33. N-gain of both classes is in the medium classification. Effect size test results of 0.22 are in the classification of low effects so that the difference in the increase in physics learning outcomes of students in the experimental class and the control class is not significant.